Factors That Influence Adherence to Breast Tumor Patients at Surgical Clinic in The Bhayangkara Brimob Hospital - Sri Ratu Anastasya; Elfira Sri Futriani (Universitas Malahayati Lampung, 2024)
ABSTRACT The impact of pre-operative anxiety is that pre-operative anxiety can cause physical and psychological changes which ultimately activate the sympathetic autonomic nerves, thereby increasing heart rate, blood pressure, respiratory frequency, and generally reducing energy levels in the patient, and ultimately can be detrimental to the patient. itself because it will have an impact on the implementation of operations. To determine the relationship between therapeutic communication and the level of anxiety of primigravida mothers in facing SC delivery at Bhayangkara Brimob Hospital in 2023. The research approach used in this research is cross-sectional. The population in this study was 30 women pre-SC surgery. The sample in this study was 30 people. The sampling technique is total sampling. Researchers used the Chi Square test. The research results showed that the majority's anxiety level was moderate anxiety level at 46.7%. The majority of therapeutic communication is good therapeutic communication as much as 63.3%. From the statistical test results, it was found that P value = 0.002, meaning P value α (0.05). There is a relationship between therapeutic communication and the level of anxiety of primigravida mothers in facing SC delivery at Bhayangkara Brimob Hospital in 2023. Suggestions for hospitals to create educational classes for pregnant women before delivery regarding the birth process Keywords: Communication, Anxiety, Sectio Caesarea